Preclinical Therapy with Vitamin D3 in Experimental Encephalomyelitis: Efficacy and Comparison with Paricalcitol - Mimura, Luiza Ayumi Nishiyama (Int J Mol Sci, 2021)
Multiple sclerosis (MS) is a chronic demyelinating disease of the central nervous system (CNS). MS and its animal model called experimental autoimmune encephalomyelitis (EAE) immunopathogenesis involve a plethora of immune cells whose activation releases a variety of proinflammatory mediators and free radicals. Vitamin D3 (VitD) is endowed with immunomodulatory and antioxidant properties that we demonstrated to control EAE development. However, this protective effect triggered hypercalcemia. As such, we compared the therapeutic potential of VitD and paricalcitol (Pari), which is a non-hypercalcemic vitamin D analog, to control EAE. From the seventh day on after EAE induction, mice were injected with VitD or Pari every other day. VitD, but not Pari, displayed downmodulatory ability being able to reduce the recruitment of inflammatory cells, the mRNA expression of inflammatory parameters, and demyelination at the CNS. Lower production of proinflammatory cytokines by lymph node-derived cells and IL-17 by gut explants, and reduced intestinal inflammation were detected in the EAE/VitD group compared to the EAE untreated or Pari groups. Dendritic cells (DCs) differentiated in the presence of VitD developed a more tolerogenic phenotype than in the presence of Pari. These findings suggest that VitD, but not Pari, has the potential to be used as a preventive therapy to control MS severity.